2014
DOI: 10.1021/es5040156
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions from Process Equipment at Natural Gas Production Sites in the United States: Pneumatic Controllers

Abstract: Emissions from 377 gas actuated (pneumatic) controllers were measured at natural gas production sites and a small number of oil production sites, throughout the United States. A small subset of the devices (19%), with whole gas emission rates in excess of 6 standard cubic feet per hour (scf/h), accounted for 95% of emissions. More than half of the controllers recorded emissions of 0.001 scf/h or less during 15 min of measurement. Pneumatic controllers in level control applications on separators and in compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(178 citation statements)
references
References 18 publications
3
169
1
Order By: Relevance
“…Similarly, multiple studies (Prasino 2013; Allen et al, 2015a;Gibbs, 2015) have found that a small subpopulation of pneumatic controllers (the largest source of greenhouse gases in the petroleum and natural gas supply chains) dominates emissions. Allen et al (2015a), for example, estimated that 20% of pneumatic controllers in a national sampling of natural gas sites account for 95% of pneumatic controller emissions, and Gibbs (2015) found that 3.5% of controllers accounted for 73% of controller emissions at sites sampled in Oklahoma.…”
Section: Zavala Et Al 2015amentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, multiple studies (Prasino 2013; Allen et al, 2015a;Gibbs, 2015) have found that a small subpopulation of pneumatic controllers (the largest source of greenhouse gases in the petroleum and natural gas supply chains) dominates emissions. Allen et al (2015a), for example, estimated that 20% of pneumatic controllers in a national sampling of natural gas sites account for 95% of pneumatic controller emissions, and Gibbs (2015) found that 3.5% of controllers accounted for 73% of controller emissions at sites sampled in Oklahoma.…”
Section: Zavala Et Al 2015amentioning
confidence: 98%
“…Recent field studies have sought to quantify these uncertainties. For example, Allen et al (2015a) assessed differences between observed and inventoried pneumatic controller activity factors and reported a factor of 2-3 difference between observed numbers of pneumatic controllers per well Aircraft-based measurements upwind and downwind of production regions; methane measured using high-precision, high-time-resolution instruments, absorption spectrometry at precise infrared wavelengths; light alkanes analyzed from discrete air samples Emissions (0.48 ± 0.13 Tg/yr) 6.2-11.7% of natural gas production Bottom-up inventories for cattle and gas seepage were subtracted from total emissions; difference assigned to oil and gas activity based on methane to light-alkane ratios Barnett Shale Karion et al, 2015 Aircraft-based measurements upwind and downwind of production regions; methane measured using high-precision, high-time-resolution instruments, absorption spectrometry at precise infrared wavelengths…”
Section: Comparisons Of Emission Estimates With Measurementsmentioning
confidence: 99%
“…For example, a number of studies report on direct GHG measurements from individual facilities. These include direct stack measurements of power plant CO 2 emissions (e.g., Teichert et al, 2003) and numerous recent studies of CH 4 emissions from oil and gas operations: measurements of emissions from pneumatic controllers (Allen et al, 2015), compressor stations , transmission and storage systems , and abandoned wells (Kang et al, 2014). In addition, several site-level studies target agricultural emissions.…”
Section: Recent Direct Measurements That Support Bottom-up Effortsmentioning
confidence: 99%
“…For example, facility-level observations provide the most insight into detailed emission processes from specific source sectors but can miss emission events or processes. Observations of oil and gas facilities provide a prime example; scientists may not know about some leaks and therefore may not measure them, other leaks may be in inaccessible locations (e.g., Subramanian et al, 2015), and the largest leaks often come from ephemeral equipment failures at a small number of facilities that are difficult to identify (e.g., Brantley et al, 2014;Allen, 2014;Allen et al, 2015). Cost also limits facility-level, continuous emission monitoring; it is typically only used for large point sources like power plants (National Research Council, 2010).…”
Section: Recent Direct Measurements That Support Bottom-up Effortsmentioning
confidence: 99%
“…For example, point sources of anthropogenic emissions can be measured directly at discrete times (e.g., Allen et al, 2015;Subramanian et al, 2015;Zimmerle et al, 2015),…”
Section: Introduction and The Need For Diagnosticsmentioning
confidence: 99%